Plant microbiota: from model plants to Mediterranean crops - CHIALVA, Matteo; BONFANTE, Paola (Phytopathologia Mediterranea, 2018)
Plants live in ecosystems where they interact with complex microbial communities instigating a wide range of relationships. These communities constitute the ‘microbiota’, a term initially coined to describe host-symbiont systems that has been extended to cover non-symbiotic, but mostly beneficial interactions. Through the development of innovative ‘-omics’ technologies such as high-throughput sequencing, study of plant microbiota has advanced rapidly, allowing scientists to increase understanding of plant primary functions and how these can be positively impacted by microbes. In addition, basic knowledge of plant-microbe interactions offers novel potential applications for sustainable agriculture. This review outlines new concepts of the ’plant metagenome‘, then summarizes major advances related to plant root-associated microbial communities, from model plants, such as Arabidopsis thaliana, to important Mediterranean crops. Arbuscular mycorrhizal fungi are crucial components of root microbiota: they are acknowledged as relevant tools for improving plant mineral nutrition in agricultural environments. Particular attention is given to their impacts on plant hosts, particularly tomato, which has been widely used as valuable model, both in plant biology and crop sciences, due to its importance in Mediterranean agriculture.